Lee Model of Geriatric Palliative Care - Lee, Susan (2018)
The model is based in the theory of human caring authored by Dr. Jean Watson. This theory honors autonomy, choice, and meaning through deep human connection. The Caritas field is the “inner world of practice at the heart level”. The model has four domains. The first one is most important. Is the health care that the person is receiving—the treatments, the surgery, the chemotherapy, the medications—aligned with the person’s wishes, preferences, and values.